THE EFFECT OF DATA-REUSE TRANSFORMATIONS ON MULTIMEDIA APPLICATIONS FOR APPLICATION SPECIFIC PROCESSORS - Vassiliadis, N.; Chormoviti, A.; Kavvadias, N.; Nikolaidis, S. (International Journal of Computing, 2014)
Multimedia applications are characterized by a high number of data transfers and storage operations. Appropriate transformations can be applied at the algorithmic level to improve crucial implementation characteristics. In this paper, the effect of data-reuse transformations on power consumption and performance of multimedia applications, realized on an Application Specific Instruction set Processor (ASIP), is examined. An ASIP for multimedia applications designed based on a complete methodology is used to evaluate this effect. Results prove the efficiency of the ASIP solution and indicate benefits from the use of the data-reuse transformations in terms of energy consumption and performance. Also, preliminary results from the exploitation of instruction buffering technique to reduce the energy consumption of the ASIP are presented.